Potential side effects of medicine on patients with tuberculosis fixed-dose combination in dr. Pirngadi Hospital, Medan - EVA SARTIKA DASOPANG; FENNY HASANAH; IDA FAUZIAH; SALMAN SALMAN; TEDY KURNIAWAN BAKRI (Jurnal Natural, 2020)
Tuberculosis is caused by the bacterium Mycobacterium tuberculosis, which by only using a few new antibiotics, can kill the bacteria. Tuberculosis treatment has several stages, namely intensive and advanced stages. Compliance with the use of OAT is an imported factor in the success of TB treatment. The use of many drugs can cause side effects that result in patients stopping treatment when it creates the TB treatment process to fail. Improved adherence can do by using a fixed-dose combination OAT. In the intensive phase, the patient will get a fixed-dose combination containing a mixture of four antibiotics. The purpose of this study is to evaluate the potential side effects that occur during fixed-dose combination OAT treatment at an intensive stage and see the level of compliance of patients taking TB drugs. Observational sampling in TB patients was taking OAT at an acute stage by looking at side effects that arise during treatment and then analyzed using statistics and algorithm Naranjo. The results showed the most common potential side effects for fixed-dose combination OAT in the intensive stage were itching, headache and nausea with a percentage of 72% each, joint pain 45%, stomach pain 36.4%, lack of appetite and rashes 27.3% each and reddish color in the urine 18.2%. The results of the analysis using Naranjo logarithm obtained results eight, which means the side effects might cause due to the use of the drug. The results of patient compliance achieved a 100% compliance rate